Combined use of medically-assisted reproductive techniques: a new bioethical issue - Bertelli, Matteo; Paolacci, Stefano; Placidi, Giorgio; Scaccia, Gino; Chiurazzi, Pietro; Fulcheri, Ezio; Malacarne, Daniele; Lichterman, Boleslav; Petralia, Paolo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: The studies of Nobel laureate Robert Geoffrey Edwards led to the first in vitro fertilization and embryo transfer in 1978. Since then, reproductive medicine has made huge advances. Methods available to sterile couples now include: purchasing oocytes and sperm, uterus surrogacy, pre-implantation or pre-natal diagnosis, embryo/fetal selection. Here we highlight the fact that combinations of existing technologies could threaten the non-marketability of human life. Methods: We searched PubMed and websites to find articles regarding assisted reproduction techniques. Results: These methods, taken separately, provide support for natural fertilization, but when used together, they may lead to genuine “baby factories”. In poor countries, such “factories” exist and often act illegally. Conclusions: We highlight the need for deeper bioethical studies and better legislation regarding the combined use of medically-assisted reproductive techniques.